2014
DOI: 10.3402/tellusb.v66.23037
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fine-mode AOD and precipitation on seasonal and interannual time scales

Abstract: A B S T R A C T On seasonal and interannual time scales, weather is highly influential in aerosol variability. In this study, we investigate the relationship between fine-mode AOD (fAOD) and precipitation on these scales, in order to unravel the effect of wet weather on aerosol amount. We find with integrated satellite and ground observations that biomass burning related fAOD has a relatively greater seasonal variation than fossil fuel combustion related fAOD. It is also found that wet weather reduces biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…These pollutants alter the regional climate of downwind areas by altering ambient temperature, cloud properties, and precipitation efficiency (Jeong et al, 2008;Youn et al, 2011;Jeong et al, 2014). They also influence the air quality of downwind areas in urban, ocean, and Arctic regions through long-range atmospheric transport (Carvalho et al, 2011;Quennehe et al, 2012;Schreier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These pollutants alter the regional climate of downwind areas by altering ambient temperature, cloud properties, and precipitation efficiency (Jeong et al, 2008;Youn et al, 2011;Jeong et al, 2014). They also influence the air quality of downwind areas in urban, ocean, and Arctic regions through long-range atmospheric transport (Carvalho et al, 2011;Quennehe et al, 2012;Schreier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies counted haze days based on atmospheric visibility and found that El Niño events could induce more (fewer) winter haze days in northern (southern) China (Gao and Li, 2015;Li et al, 2017). In addition to surface observations, several studies have also analyzed the relationship between ENSO events and aerosol loading based on aerosol optical depth (AOD) data from satellite retrievals (Jeoung et al, 2014;Sun et al, 2018). Jeoung et al (2014) analyzed the combined AOD data of MODIS (Moderate Resolution Imaging Spectroradiometer), MISR (Multi-angle Imaging SpectroRadiometer) and AERONET (AErosol RObotic NETwork) and found that, during the warm phase of ENSO, the fine-mode AOD increased in eastern coastal areas but decreased in some inland areas of China.…”
Section: Introductionmentioning
confidence: 99%
“…LRT haze can also affect the regional radiation budget directly by scattering or absorbing solar radiation and indirectly by altering the physical properties of clouds and the efficiency of precipitation (Ramanathan et al, 2007;Gao et al, 2014;Jeong et al, 2014;Jung et al, 2015). Zhang et al (2007) reported that the Asian pollution outflow influences precipitation over the North Pacific.…”
Section: Introductionmentioning
confidence: 99%